The influence of firm age and intangible resources on the relationship between entrepreneurial orientation and firm growth among Japanese SMEs - Anderson, Brian S.; Eshima, Yoshihiro (Journal of Business Venturing, 2013)
With the relationship between entrepreneurial orientation (EO) and firm performance having broad scholarly acceptance, researchers are now delving with increased focus into the contextual factors that change the nature of the relationship between EO and various manifestations of organizational performance. In this vein, this study adopts the resource based view and investigates the moderating influence of firm age and intangible resources on the EO-firm growth relationship among small to medium sized enterprises (SMEs) in Japan. Further, we propose a three-way interactive model between EO, firm age, and intangible resources to better identify entrepreneurial configurations that promote superior SME growth.